Application of Character Education Values in Early Childhood Through Online Fables - Iswandi Afandi; Juanda Juanda (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
The purpose of this study is to describe the types of characters contained in online fables with children's literary approaches and character education. Research methods, namely descriptive qualitative with content analysis techniques. Data analysis was performed using content analysis and descriptive techniques. Data collection is based on literature. The data source, which is 5 fables with the character education theme, is downloaded online via the web https://dongengceritarakyat.com/. The types of characters found are described in detail according to the quotations found in the fable. Data analysis was carried out through the stages of data reduction, data presentation, concluding, and verification of research results. The results of the study found seven-character values ​​as follows: (1) fable Crocodile and Singer Bird found polite and friendly characters; (2) Arrogant fable leaves are found to be humble and environmentally conscious characters; (3) the Young Mouse fable is found to be a character of curiosity; (4) fable Herders and Wild Goats found fair characters; and (5) the fable of contention of bees and wasps found wise character. Abstrak Iswan Afandi & Juanda; Application of Character Education ... Tujuan penelitian ini adalah mendeskripsikan jenis karakter yang terdapat dalam fabelonline dengan pendekatan sastra anak dan pendidikan karakter. Metode penelitian, yaitu kualitatif deskriptif dengan teknik analisis isi. Analisis data dilakukan dengan teknik analisis isi dan teknik deskriptif. Pengumpulan data dilakukan berdasarkan kepustakaan. Sumber data, yaitu5fabelbertema pendidikan karakterdi unduh secara online melalui web https://dongengceritarakyat.com/. Jenis karakter yang ditemukan dideskripsikan secara terperinci sesuai dengan kutipan yang ditemukan dalam fabel. Analisis data dilakukan melalui tahapanreduksi data, penyajian data, pengambilan simpulan, dan verifikasi hasil penelitian. Hasil penelitian ditemukan tujuh nilai karakter sebagai berikut: (1) fabelBuaya dan Burung Penyanyiditemukan karakter sopan dan bersahabat; (2) fabelDaun yang Sombongditemukan karakter rendah hati dan peduli lingkungan; (3) fabel Tikus Muda ditemukan karakter rasa ingin tahu; (4) fabel Penggembala dan Kambing Liar ditemukan karakter adil; dan (5) fabelPertengkaran Lebah dan Tawon ditemukan karakter bijaksana. Kata kunci: sastra anak, fabel, nilai karakter